(untitled) (Berlin, 2006)
This book constitutes the refereed proceedings of the 10th European Conference on Research and Advanced Technology for Digital Libraries, ECDL 2006, held in Alicante, Spain in September 2006. It consists of 36 revised full papers presented together with the extended abstracts of 18 demo papers and 15 revised poster papers which were carefully reviewed and selected from a total of 159 submissions. The papers focus on architectures, preservation, retrieval, applications, methodology, metadata, evaluation, user studies, modeling, audiovisual content, and language technologies.
Keywords: Digital libraries,Thư viện số; Europe,Châu Âu